Dzieci i młodzież w obliczu współczesnych zagrożeń - Muszyński, Heliodor (Pedagogika Społeczna Nova, 2025)
The subject of the article is the dangers that arise in the lives of today’s children and adolescents, leading to anxiety and depression in increasing numbers, sometimes ending in suicide attempts. The cause of this evil is seen in the so-called “smartphoneization,” and in seeking ways to prevent it, the need to ban children and adolescents from using smartphones is pointed out. In the article, this way is questioned. It presents in more detail the factors and mechanisms of these disorders and the place that smartphoneization has in it. The terrain that is the main source of the occurrence of risks is also indicated. This terrain is the school, more specifically, the school classroom, where abnormal relations between students, including cyberbullying, often occur. The main cause of these abnormalities is the school system, which is fraught with numerous flaws. The final part of the article discusses changes that would lead to its improvement.